Assessment of optical emission analysis for in-process monitoring of powder bed fusion additive manufacturing - Alexander J. Dunbar; Abdalla R. Nassar (Virtual and Physical Prototyping, 2018)
Developing methods which allow real-time monitoring of powder bed fusion (PBF) additive manufacturing (AM) processes is key to enabling in situ assessments of build quality (e.g. lack of fusion and porosity). Here, we investigate the use of optical emission spectroscopy and high-speed (100 kHz) measurement of select wavelength emissions, based on a line-to-continuum approach, to determine if a correlation between PBF AM process inputs, sensor outputs, and build quality exists. Using an open protocol system interfaced with a 3D Systems ProX 200 machine, sensor data were synchronised with the scanner position and the laser state during the buildup of Inconel-718 components under varying powers, scan speeds, and hatch spacing parameters. Sensor measurements were then compared against post-build computed tomography scans. We show evidence that sensor data, when combined with appropriate analyses, are related to both processing conditions and build quality.